ANALISIS USAHA PENGOLAHAN ABON LELE DI DESA TEGALREJO KECAMATAN SAWIT KABUPATEN BOYOLALI - Fuad Hanif NurCholis; Lutfi Aris Sasongko; Aniya Widiyani (MEDIAGRO, 2019)
ABSTRACT Shredded-catfish processing business is a business that produces floss with raw catfish as the main ingredient. The business of shredded-catfish in Boyolali Regency located in Kampung Lele, Tegalrejo Village, Sawit District. Shredded-catfish become the superior product in Boyolali and the surrounding areas. The purpose of this research are to determine the total production costs, the level of revenue, income, and feasibility of the shredded-catfish processing business in Tegalrejo Village, Sawit District, Boyolali Regency. The basic method that used in research was using descriptive analitycal method. Determination of the sample location was carried out purposely in Tegalrejo Village, Sawit District, Boyolali Regency. The data used are primary and secondary data. Data retrieval method used are interview, observation and recording. There are 23 respondents in this study from some business groups i.e Karmina, Pamuji and Alang-Alang. Data analysis method used are cost, revenue, income, R/C and BEP analysis. Research result from the study of shredded-catfish processing business in Karmina, Pamuji and Alang-Alang business group for one month respectively cost as much as Rp 24.043.591; Rp 26.055.548; and Rp 8.397.784. Those total cost consist of the cost of raw materials, fuel, packaging, depreciation of equipment, employee wages and electricity. Karmina group produces 276 kg of shredded catfish at a price of Rp 120.000/kg. Pamuji Group produces 336 kg of shredded catfish at a price of Rp 110.000/kg. Alang-Alang group produces 120 kg at a price of Rp 110.000/kg, so the total revenue of the Karmina group is Rp 33.120.000; Pamuji group’s total revenue is Rp 36.960.000; and Alang-Alang group is Rp 13.200.000. Total income of Karmina group is Rp 9.076.408; Pamuji group is Rp 10.904.451; and Alang-Alang group is Rp 4.802.215. The R/C values of the Karmina, Pamuji and Alang-Alang business group are respectively 1,37; 1.41; 1.57, so the business is feasible to do. The BEP unit value in the Karmina group is 100,36 kg, Pamuji group is 236,86 kg and Alang-Alang group is 76,34 kg, while the BEP price value in the Karmina group is Rp. 87,114.44; Pamuji group is Rp 77,546.27; and Alang-Alang group is Rp 69,981,53. Keywords: business analysis, shredded-catfish, R/C, BEP